Drogadicción y su repercusión en el comportamiento de una adolescente de 16 años del Centro de Rehabilitación Autónomo Lenin Moreno - Gutiérrez Flores, Samanta Melissa (2023)
The present case study was carried out with the objective of analyzing the repercussion of drug addiction on the behavior of a 16-year-old adolescent from the Lenin Moreno rehabilitation center. All this was carried out through the use of the clinical history, semi-structured interview, direct observation, genopro, and the application of psychological tests "Beck Depression Inventory", "Hamilton Anxiety Scale", "mini mental", and “Assist”, in addition, of the “ABC model of CBT”. On the other hand, the qualitative methodology that was used in this work was aimed at studying the dependent and independent variables, also thanks to the implementation of CBT techniques, it was possible to meet the stated objective, on the other hand, through a therapeutic plan managed to modify those thoughts that the patient expressed during the psychological intervention, in this way it was possible to mitigate the emotional problems and behavioral changes of the adolescent due to drug use, finally the results obtained were the desired ones which were aimed at improving their personal and social quality of life.